Пути повышения практической подготовки студентов по дисциплине «техническая защита информации» - Халина, О. М. (ХНУРЭ, 2009)
The given work is devoted consideration of problems of upgrading preparation of specialists with higher education, control of educational work and estimation of knowledges of students